Metode Multi-Criteria Iterative Forward Search Untuk Penjadwalan Ujian dan Pengawas Ujian - Agus Subhan Akbar; Akhmad Khanif Zyen (JUTI: Jurnal Ilmiah Teknologi Informasi, 2019)
Setting Examination schedules to support learning evaluation is crucial. The ideal scheduling for this exam must be able to allocate all related components in the implementation of the test within a predetermined time span. The components of the implementation of an examination in a university include the departments in the faculty, a number of courses and participants, the room used, the time of execution, and the lecturer serving as supervisor. The arrangement of each component of the implementation of the exam needs to be carried out appropriately so there is no collision of the schedule between the participants, the schedule, the room used, and the supervisor in charge. The purpose of this study is to produce an ideal exam scheduling and examination supervisor. The study was conducted by applying the Multi-Criteria Iterative Forward Search from the Academic Information System (SIAKAD) data at the Faculty of Science and Technology, Unisnu Jepara. This research has resulted in a system that is able to create an examination schedule and supervisory schedule that accommodates all factors without conflict, well tested, and applied.